Tree-level UV completions for N R SMEFT d = 6 and d = 7 operators - Rebeca Beltrán; Ricardo Cepedello; Martin Hirsch (Journal of High Energy Physics, 2023)
Abstract We study ultra-violet completions for operators in standard model effective field theory extended with right-handed neutrinos (N R SMEFT). Using a diagrammatic method, we generate systematically lists of possible tree-level completions involving scalars, fermions or vectors for all operators at d = 6 and d = 7, which contain at least one right-handed neutrino. We compare our lists of possible UV models to the ones found for pure SMEFT. We also discuss how the observation of LNV processes via N R SMEFT operators at the LHC can be related to Majorana neutrino masses of the standard model neutrinos.